Gender-stratified analysis of DLG5 R30Q in 4707 patients with Crohn disease and 4973 controls from 12 Caucasian cohorts. Issue 1 (10th August 2007) - Browning, B L; Annese, V; Barclay, M L; Bingham, S A; Brand, S; Büning, C; Castro, M; Cucchiara, S; Dallapiccola, B; Drummond, H; Ferguson, L R; Ferraris, A; et al.
Abstract : Background: DLG5 p.R30Q has been reported to be associated with Crohn disease (CD), but this association has not been replicated in most studies. A recent analysis of gender-stratified data from two case–control studies and two population cohorts found an association of DLG5 30Q with increased risk of CD in men but not in women and found differences between 30Q population frequencies for males and females. Male–female differences in population allele frequencies and male-specific risk could explain the difficulty in replicating the association with CD. Methods: DLG5 R30Q genotype data were collected for patients with CD and controls from 11 studies that did not include gender-stratified allele counts in their published reports and tested for male–female frequency differences in controls and for case–control frequency differences in men and in women. Results: The data showed no male–female allele frequency differences in controls. An exact conditional test gave marginal evidence that 30Q is associated with decreased risk of CD in women (p = 0.049, OR = 0.87, 95% CI 0.77 to 1.00). There was also a trend towards reduced 30Q frequencies in male patients with CD compared with male controls, but this was not significant at the 0.05 level (p = 0.058, OR = 0.87, 95% CI 0.74 to 1.01). When data from this study were combined with previously published, gender-stratified data, the 30Q allele was found to be associated with decreased risk of CD in women (p = 0.010, OR = 0.86, 95% CI 0.76 to 0.97), but not in men. Conclusion: DLG5 30Q is associated with a small reduction in risk of CD in women.